Identification of MK-8133: An orexin-2 selective receptor antagonist with favorable development properties. Issue 12 (15th June 2015) - Kuduk, Scott D.; Skudlarek, Jason W.; DiMarco, Christina N.; Bruno, Joseph G.; Pausch, Mark H.; O'Brien, Julie A.; Cabalu, Tamara D.; Stevens, Joanne; Brunner, Joseph; Tannenbaum, Pamela L.; Garson, Susan L.; Savitz, Alan T.; et al.
Graphical abstract: Molecules related to the dual orexin receptor antagonist filorexant were transformed into compounds that were selective for the OX2 R subtype leading to MK-8133. Abstract: Antagonism of orexin receptors has shown clinical efficacy as a novel paradigm for the treatment of insomnia and related disorders. Herein, molecules related to the dual orexin receptor antagonist filorexant were transformed into compounds that were selective for the OX2 R subtype. Judicious selection of the substituents on the pyridine ring and benzamide groups led to6b ; which was highly potent, OX2 R selective, and exhibited excellent development properties.